2010
DOI: 10.1111/j.1582-4934.2009.00932.x
|View full text |Cite
|
Sign up to set email alerts
|

BiP, an endoplasmic reticulum chaperone, modulates the development of morphine antinociceptive tolerance

Abstract: Morphine is a potent analgesic, but the molecular mechanism for tolerance formation after repeated use is not fully understood. Binding immunoglobulin protein (BiP) is an endoplasmic reticulum (ER) chaperone that is central to ER function. We examined knock-in mice expressing a mutant BiP with the retrieval sequence deleted in order to elucidate physiological processes that are sensitive to BiP functions. We tested the thermal antinociceptive effect of morphine in heterozygous mutant BiP mice in a hot plate te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 45 publications
(69 reference statements)
2
26
0
Order By: Relevance
“…However, the response latencies of the mutant BiP mice after the tenth morphine treatment were significantly longer than those of their wild-type littermates at 30, 45 and 60 min after injection. These results showed that the mutant BiP mice were impaired in the development of morphine tolerance (Dobashi et al, 2010).…”
Section: Morphine Tolerance Is Attenuated In Mice Expressing a Mutantmentioning
confidence: 54%
See 4 more Smart Citations
“…However, the response latencies of the mutant BiP mice after the tenth morphine treatment were significantly longer than those of their wild-type littermates at 30, 45 and 60 min after injection. These results showed that the mutant BiP mice were impaired in the development of morphine tolerance (Dobashi et al, 2010).…”
Section: Morphine Tolerance Is Attenuated In Mice Expressing a Mutantmentioning
confidence: 54%
“…Western blot revealed prominent phosphorylation at Ser9 of GSK3β and less phosphorylation at Tyr216 in the homozygous mutant BiP brain compared to those in the wild-type brain. These results suggested that the mutant BiP lacking the KDEL sequence might attenuate the activation of GSK3β in vivo (Dobashi et al, 2010).…”
Section: Inhibition Of Gsk3β Signaling Is Associated With the Preventmentioning
confidence: 75%
See 3 more Smart Citations